Erratum: Regional variation in low-value musculoskeletal surgery: a nationwide study from the Finnish Care Register - Ville Ponkilainen; Anniina Laurema; Ville M Mattila; Teemu Karjalainen (Acta Orthopaedica)
We would like to inform of an error in the reported incidences in our published article, Regional variation in low-value musculoskeletal surgery: a nationwide study from the Finnish Care Register. Specifically, the incidences for rotator cuff repair, partial meniscectomy, ankle arthroscopy, distal radius fracture fixation, and wrist arthroscopy surgeries were calculated using a too small population size.